ANALISIS PERBANDINGAN WAKTU DAN BIAYA PELAKSANAAN KONTRUKSI DECK ON PILE DAN CAKAR AYAM MODIFIKASI (Study Kasus Pekerjaan Pondasi Rubber Tyred Gantry Crane Pads Pelabuhan Trisakti Banjarmasin) (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
Trisakti II Port, located in the city of Banjarmasin, South Kalimantan, is one of the ports that uses RTG cranes. Constraints often arise due to the lack of support for the container/CY stockpiling field due to the elevation of the field under the highway. So that when it rains, the container yard is often flooded, causing physical damage to the container and its cargo. And the type of soil in the study area is soft soil, so planning for a good and efficient foundation structure is needed. The purpose of writing this thesis is to determine the comparison of the costs and construction time used in the modified deck on pile and chicken claw structures. Determine which is more efficient between the deck on pile foundation structure and modified chicken claw. With the method of comparing the total cost of the budget and the time required for the implementation of construction. The results of this study are the results of the comparison of time and cost of deck on pile and modified chicken claw on the RTG Pad foundation work is the modified chicken claw foundation structure is 15% more efficient and 26% faster in execution time with a labor ratio that only differs 1 people per day. In terms of time and cost between deck on pile and modified chicken claw, it is found that the use of modified chicken claw structure is more efficient than deck on pile structure in this RTG Pad foundation work.